simplify 3(4h^5 - k^4)-(5h^5 + 2k^4)

Question

Asked 5/10/2013 1:44:03 PM

Updated 8/12/2014 1:27:53 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Edited by andrewpallarca [8/12/2014 1:26:28 PM], Flagged by andrewpallarca [8/12/2014 1:27:53 PM]

SOLUTION:

3(4h^5-k^4)-(5h^5+2K^4).

12h^5-3k^4-5h^5+2K^4 .

12h^5-5h^5-3k^4+2K^4 .

7h^5 - k^4.

Question

Asked 5/10/2013 1:44:03 PM

Updated 8/12/2014 1:27:53 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Edited by andrewpallarca [8/12/2014 1:26:28 PM], Flagged by andrewpallarca [8/12/2014 1:27:53 PM]

Rating

3

3(4h^5 - k^4) - (5h^5 + 2k^4)

= (12h^5 - 3k^4) - (5h^5 - 2k^4)

= (12h^5 - 3k^4) + (-5h^5 - 2k^4)

= 7h^5 - 5k^4

= (12h^5 - 3k^4) - (5h^5 - 2k^4)

= (12h^5 - 3k^4) + (-5h^5 - 2k^4)

= 7h^5 - 5k^4

Added 8/12/2014 1:27:51 PM

This answer has been confirmed as correct and helpful.

evaluate gh-k wheng=-8, h=4, and k=-2 **Weegy:** gh-k, (-8)(4) +2, -32 + 2 = -30 (More)

Question

Expert Answered

Updated 8/12/2014 1:29:43 PM

0 Answers/Comments

simplify (5-p^2-4q)-(-2 q-3p^2) **Weegy:** (5-p^2-4q)-(-2+q-3p^2) = 2p^2-5q+7 (More)

Question

Expert Answered

Updated 8/12/2014 1:25:35 PM

1 Answer/Comment

(5 - p^2- 4q) - (-2q- 3p^2)

= (5 - p^2 - 4q) + (2q + 3p^2)

= 5 + 2p^2 - 2q

= 2p^2 - 2q + 5

= (5 - p^2 - 4q) + (2q + 3p^2)

= 5 + 2p^2 - 2q

= 2p^2 - 2q + 5

Added 8/12/2014 1:25:34 PM

This answer has been confirmed as correct and helpful.

Rated good by jeifunk

31,978,210

questions answered

There are no comments.